Integration of Blockchain and Fintech in Revolutionizing ‎The Indian Banking Sector: A Data-Driven Study - Shah , Aditee Huparikar; Chawla , Dr. Namita; Bhinge , Monalisa; Bhope , Dr. Anagha; Deshmukh , Dr. Prajakta B.; Deokar , Ashok; Bhojne , Mrs. Aditi Adeep (International Journal of Accounting and Economics Studies, 2025)
The integration of FinTech solutions with Blockchain technology has transformed the Indian ‎banking sector, improving operational efficiency, security, and customer experience. This study ‎examines the perspectives, cognizance, and preparedness of stakeholders with respect to the ‎integration of blockchain and fintech into banking services. A structured survey using a ‎questionnaire was conducted with 230 participants, including customers, professionals, and ‎banking employees. The analysis assessed the effects of technological integration on ‎transparency, cost-efficiency, transaction speed, and trustworthiness in banking services. The ‎findings demonstrate a significant positive disposition towards the integration of Blockchain and ‎FinTech, with primary obstacles recognized as insufficient awareness, inadequate infrastructure, ‎and unclear regulations. The research provides valuable insights for policymakers, financial ‎institutions, and FinTech startups to jointly promote the transformation of digital banking in ‎India‎.
Keywords: Blockchain; FinTech; Indian Banking Sector; Digital Transformation; Financial ‎Technology; Distributed Ledger